Minat Belajar Anak dan Respon Orang Tua terhadap Pendampingan Belajar pada Masa Covid-19 (Studi Kasus Kecamatan Pahandut Palangka Raya) - Hadi Kusuma, Muhammad Prayoga; Setyowati, Ais Rantauni; Wati, Helda; Tumini, Tumini; Maulida, Elyami; Raniah, Nor; Fitriani, Amelia; Damayanti, Annisa; Hasbi, Artani; Yusuf, Muhammad; Hujjatusnaini, Noor (Madani: Jurnal Pengabdian Ilmiah, 2020)
This study aims to determine student interest in learning and parents' responses to learning assistance at home during the Covid-19 pandemic in Pahandut Palangka Raya District, Central Kalimantan. This research is a quantitative descriptive study with a survey method, in which the survey data is measured quantitatively and then the statistical correlation is sought. The research sample of students and parents of students respectively as many as 348 people. The sampling technique was purposive sampling, in the Pahandut District, Palangka Raya. The results of the study reported that students' interest in learning was in the "good enough" category, where the response of parents to children's learning assistance during the Covid-19 pandemic also showed a response in the "positive" category. Analysis of the results of variance shows very significant data (0.000 <0.05), which is interpreted as a positive correlation between student interest in learning and parental responses, which is 58% influencing children's interest simultaneously.